Principality of Andorra : 2022 Article IV Consultation-Press Release; and Staff Report. - International Monetary Fund. European Dept.. (Washington, D.C. : International Monetary Fund, 2022)
The Andorran economy is recovering strongly from the pandemic, supported by a rebound in tourism, retail trade, construction, and professional services. Real GDP is expected to reach pre-crisis levels in the second half of 2022. While the unemployment rate is amongst the lowest in Europe and continues to decline, pockets of vulnerability remain. Notwithstanding significant policy buffers, there are still substantial downside risks, notably the impact in Europe of the war in Ukraine, higher than expected inflation, and a resurgence of infection rates.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Andorra, Principality of